2006
DOI: 10.1158/0008-5472.can-06-2337
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Profiling of Primary Breast Cancer Predicts Axillary Lymph Node Metastasis

Abstract: To determine if protein expression in primary breast cancers can predict axillary lymph node (ALN) metastasis, we assessed differences in protein expression between primary breast cancers with and without ALN metastasis using surfaceenhanced laser desorption/ionization time-of-flight mass spectrometry (SELDI-TOF-MS). Laser capture microdissection was performed on invasive breast cancer frozen sections from 65 patients undergoing resection with sentinel lymph node (SLN) or level I and II ALN dissection. Isolate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
4

Year Published

2007
2007
2012
2012

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 40 publications
1
22
0
4
Order By: Relevance
“…Another study examined laser-microdissected invasive breast cancer cells and identified 2 proteins whose expression correlated with lymph node involvement. Interestingly, one of them (with low expression in node-positive disease) had an m/z ratio of 8.5 kDa, consistent with ubiquitin [94] . We have recently profiled the cytosol of 27 human breast cancer cell lines [95] .…”
Section: Seldi-and Maldi-based Protein Profiling Of Clinical Samplesmentioning
confidence: 63%
“…Another study examined laser-microdissected invasive breast cancer cells and identified 2 proteins whose expression correlated with lymph node involvement. Interestingly, one of them (with low expression in node-positive disease) had an m/z ratio of 8.5 kDa, consistent with ubiquitin [94] . We have recently profiled the cytosol of 27 human breast cancer cell lines [95] .…”
Section: Seldi-and Maldi-based Protein Profiling Of Clinical Samplesmentioning
confidence: 63%
“…Currently, the use of proteomics research on tumor metastasis in prostate cancer (Pang et al, 2010), colon cancer (Xue et al, 2010), multiple myeloma (Wang et al, 2009) and larynx cancer (Cheng et al, 2008) have been successfully reported, but few studies have been reported in axillary lymph node metastasis of breast cancer. Nakagawa et al (2006) reported the use of Surface-enhanced laser desorption and ionization time-offlight mass spectrometry (SELDI)-TOF-MS combined with microdissection to detect 65 cases of primary breast cancer and found that protein m/z peaks at 4871 and 8596 Da were associated with axillary lymph node metastasis. Hu and colleagues used two-dimensional liquid chromatography tandem MS (2D-LC-MS/MS) to detect seven lymph node-positive cases and seven lymph nodenegative cases in breast cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…Another SELDI-TOF MS study using LCM, analyzed the tumor tissues of 65 patients with or without axillary compromise and identified two peaks (4,871 and 8,596 Da) differentially expressed for the conditions; the 8,596 Da peak corresponded to ubiquitin. This peak was under-expressed in breast cancers with axillary lymph node metastasis, indicating that ubiquitin is a good prognostic biomarker (55). Ubiquitin was differentially expressed in two further cell lineage studies (56).…”
Section: Prognostic and Predictive Marker Protein Profiling Studiesmentioning
confidence: 96%